Familial dyskeratotic comedones: A rare entity - Raghu Ram Maddala; Ashok Ghorpade; Mercy Polavarpu; Satish A Adulkar; Manbendra Das (Wolters Kluwer Medknow Publications, 2016)
Familial dyskeratotic comedones is an inherited disorder with distinctive clinical features and a disease course that is refractory to treatment. It is clinically characterized by numerous, discrete, disseminate, hyperkeratotic papules and comedones. On histopathology, it shows crater-like invaginations filled with keratinous material and evidence of dyskeratosis. We report here one family from central India with this rare disorder.